Three‐Dimensional Printed Model Fabrication and Effectiveness Evaluation in Fetuses With Congenital Heart Disease or With a Normal Heart. (20th June 2020) - Huang, Jia; Shi, Hua; Chen, Qian; Hu, Jiaqi; Zhang, Yuguo; Song, Hongning; Zhou, Qing
Abstract : Objectives: The purpose of this study was to investigate the technical feasibility and accuracy of applying 3‐dimensional (3D) printing of normal and abnormal fetal hearts based on spatiotemporal image correlation (STIC) volume‐rendered data. Methods: Spatiotemporal image correlation volume images of 15 healthy fetuses and 15 fetuses with cardiac abnormalities were collected, and Mimics software (Materialise NV, Leuven, Belgium) was used to postprocess the volume data to obtain a 3D digital model of fetal heart and large blood vessel morphologic characteristics and to output the file to a 3D printer for printing the 3D model of the fetal heart and large blood vessels. The effect accuracy of the 3D printed model was qualitatively evaluated by showing the 3D anatomic structure of the model combined with echocardiographic or autopsy results, and the dimensional accuracy of the 3D printed model was quantitatively evaluated by comparing the measured data of the model and echocardiography. Results: In all 30 fetuses, STIC volume data of the fetal heart were successfully reprocessed and printed out, which could visually display the morphologic characteristics of the fetal heart chamber and passage of the great vessels under normal and abnormal pathologic conditions. No significant differences in all of the heart size parameters were found between the 3D digital model, 3D printed model, and routine echocardiographic images (all P > .05). Moreover, the size parameters were concordant well between the methods, and all of the data points fell within the limits of agreement. Conclusions: It is feasible to 3D print the fetal heart using STIC volumetric images as the data source, and the 3D printed model can fully and accurately display abnormal anatomic structures of the heart.